PELAKSANAAN MASSAGE DAN GYM PADABALITA DIPOSYANDU KEDOYO - Nuridayanti, Anik; Wahyuningsih Setiawan, Atik; Restiya Agustin, Erda (Stikes Yarsi Mataram, 2025)
Toddler age is a golden age as well as a period of growth and development for children. It is s aid to be the golden age because the child's development periodis very short and can not berepeated. The aim of providing counseling and demonstrations ofmassage and gym to mothers and toddler sisto increase knowledge and skills that can help mothers and toddlers to increase the knowledge and skills of mothers doing massage and gym to increase the weight and development of toddlers. Methods of providing massage and gym with counseling and demonstration. Results: Providing counseling and demonstrations of massage and gym toi ncrease the weight and development of toddlers. The conclusion from providing counseling and demonstrations of massage and gym can increase mothers' knowledge and skills and increase the weight and development of toddlers.